The making of the "Rape of Nanking" history and memory in Japan, China, and the United States - Yoshida, Takashi, 1963- (Studies of the Weatherhead East Asian Institute, Columbia University., 2006)
This volume examines how the views of the so-called Rape of Nanking, or the Nanking Massacre, have evolved in history writing and public memory in Japan, China, and the United States, from 1937.